Continuing health care education: concepts and practices of nurses in basic health units - Priscila Orlandi Barth; Marines Aires; José Luis Guedes dos Santos; Flávia Regina Souza Ramos (Universidade Federal de Goias, 2014)
Continuing education in health care is a strategy for constructing new health care and nursing practices. This study aimed to identify the concepts and practices of continuing education in health held by primary care nurses in the municipalities of the 19th Regional Health Coordination of Rio Grande do Sul, Brazil. It was a descriptive exploratory study of quantitative approach. Data were collected through semi-structured interviews with 28 nurses and analyzed using Thematic Analysis. The results displayed that nurses have questions about the meaning and practice involved in continuing health care education, continuing education and health care education. Although continuing health care education is a public policy, it is still carried out in a fragmented and inflexible way. Professionals must have a clear idea this policy's directionality in order for health care practices to be transformed. doi: 10.5216/ree.v16i3.22020.